Durability of SARS-CoV-2 Specific IgG Antibody Responses Following Two Doses of Match and Mixed COVID-19 Vaccines Regimens in Saudi Population - Mubarak A; Almutairi S; Al-Dhabbah AD; Aldabas SY; Bhat R; Alqoufail MM; Abdel-Maksoud MA; Almanaa TN; Farrag MA; Alturaiki W (Infection and Drug Resistance, 2022)
Ayman Mubarak,1 Saeedah Almutairi,1 Abulrahman D Al-Dhabbah,1 Shaha Y Aldabas,1 Rauf Bhat,1 Mahfoudh M Alqoufail,1 Mostafa A Abdel-Maksoud,1 Taghreed N Almanaa,1 Mohamed A Farrag,1 Wael Alturaiki2 1Department of Botany and Microbiology, College of Science, King Saud University, Riyadh, 11451, Saudi Arabia; 2Department of Medical Laboratory Sciences, College of Applied Medical Sciences, Majmaah University, Majmaah, 11952, Saudi ArabiaCorrespondence: Wael Alturaiki, Email w.alturaiki@mu.edu.saBackground: SARS-CoV-2 pandemic continues to threaten the human population with millions of infections and deaths worldwide. Vaccination campaigns undertaken by several countries have resulted in a notable decrease in hospitalization and deaths. However, with the emergence of new virus variants, it is critical to determine the longevity and the protection efficiency provided by the current authorized vaccines.Aim: The aims of this study are to provide data about the magnitude of immune responses in individuals fully vaccinated against COVID-19 in Riyadh province of Saudi Arabia. Also, to evaluate the continuity of specific IgG levels and compare the titers in individuals who have been received two doses of the matched and mixed vaccines, including Pfizer and AstraZeneca against SARS-CoV-2 during the period of three to six months. Moreover, we analyze the current state of immune response in terms of antibody responses in thepopulation postvaccination using homogenous or hetrogenous vaccine regimen.Methods: A total of 141 healthy volunteers were recruited to our study; blood (n=63) and the saliva samples (n=78) and were collected from fully vaccinated individuals in Riyadh city. We employed a specific ELISA assay in plasma and saliva of fully vaccinated individuals.Results: IgG levels varied with age groups with the highest concentration in the age group 19– 29 years, but the age group (≥ 50) had the lowest IgG concentration. The IgG levels in both serum and saliva were higher after three months and start to wane after six months. Individuals who received mixed types of vaccines had significantly better response than Pfizer vaccine alone.Conclusion: The current study investigates the status of humoral responses in different age groups, in terms of antibody measurements. These data will help to evaluate the need for further COVID-19 vaccine doses and to what extent a two-dose regimen will protect vaccinated individuals.Keywords: SARS-CoV-2, antibody titer, anti-spike IgG antibody, Pfizer vaccine, AstraZeneca vaccine